Systemic amyloidosis in transgenic mice carrying the human mutant transthyretin (Met30) gene. Pathologic similarity to human familial amyloidotic polyneuropathy, type I. - Yi, S. (1991)
To analyze the pathologic processes of amyloid deposition in type I familial amyloidotic polyneuropathy (FAP), mice were made transgenic by introducing the human mutant transthyretin (TTR) gene. In these transgenic mice, amyloid deposition started in the gastrointestinal tract, cardiovascular system, and kidneys 6 months after birth and extended to various other organs and tissues with advancing age. At age 24 months, the pattern of amyloid deposition was similar to that observed in human autopsy cases of FAP, except for its absence in the choroid plexus and in the peripheral and autonomic nervous systems. Amyloid deposition was shown to be composed of human mutant TTR and, in addition, mouse serum amyloid P component. These results clearly indicate that human variant TTR produced in transgenic mice deposits is a major component of amyloid fibrils in various organs and tissues. Thus this animal model is useful for analyzing how amyloid deposition initiates and proceeds in FAP.